A comparative analysis of incident reporting lag times in academic medical centres in Japan and the USA. Issue 6 (1st March 2010) - Regenbogen, S E; Hirose, M; Imanaka, Y; Oh, E-H; Fukuda, H; Gawande, A A; Takemura, T; Yoshihara, H
Abstract : Background: Delays in reporting of medical errors may signal deficiencies in the performance of hospital-based incident reporting. We sought to understand the characteristics of hospitals, providers and patient injuries that affect such delays. Setting and Methods: All incident reports filed between May 2004 and August 2005 at the Kyoto University Hospital (KUH) in Japan and the Brigham and Women's Hospital (BWH) in the USA were evaluated. Lag time between each event and the submission of an incident report were computed. Multivariable Poisson regression with overdispersion, to control for previously described confounding factors and identify independent predictors of delays, was used. Results: Unadjusted lag times were significantly longer for physicians than other reporters (3.6 vs 1.8 days, p<0.0001), longer for major than minor events (4.1 vs 1.9 days, p=0.0006) and longer at KUH than at BWH (3.1 vs 1.0 days, p<0.0001). In multivariable analysis, lag times at KUH remained nearly three times longer than at BWH (incidence–rate ratio 2.95, 95% CI 2.84 to 3.06, p<0.0001). Conclusions: Lag time provides a novel and useful metric for evaluating the performance of hospital-based incident reporting systems. Across two very different health systems, physicians reported far fewer events, with significant delays compared with other providers. Even after controlling for important confounding factors, lag times at KUH were nearly triple those at BWH, suggesting significant differences in the performance of their reporting systems, potentially attributable to either the ease of online reporting at BWH or to the greater attention to patient safety reporting in that hospital.